Working memory, sustained attention, and physical activity: An intraindividual study. (May 2022) - Trevillion, Charlotte; Malmberg, Lars-Erik; Esser, Patrick
Abstract: Objective: Experimental studies show small to moderate effects of both acute and regular physical activity on executive functions, these being strongly associated with academic performance at school. In order to understand the naturally occurring associations between primary school-aged children's working memory, self-reported sustained attention, and physical activity, 35 children (M age = 9.8 years, range = 7.6–11.4 years old) in Years 3–6 of primary school took part in a two-week long intraindividual study. Methods: Participants wore an accelerometer wristband throughout the study, and carried out a working memory task (digit recall) and completed a sustained attention measure each morning and afternoon, giving 517 time-points nested in 4–10 school-days (M obs = 15.8 situations, n obs = 4–18). Results: Using multilevel structural equation models (MSEM), we found that working memory was stable across time (within-person b = 0.29) and trait-like ( ICC s = 0.58). Across situations, state-working memory was higher later in the calendar week. Acute moderate to vigorous physical activity (MVPA) was not associated with state-working memory, but exertion of a higher level of MVPA than usual the previous day was associated with lower state-working memory the following day. Trait-sustained attention (across the two weeks) predicted higher trait-working memory and older students outperformed younger students. Conclusions: Implications for timing and intensity of students' physical activity in educational settings is discussed. Highlights: Individual differences in the relationship between working memory and sustained attention. Increased MVPA on the day before was followed by decreased working memory the next day. Increased self-reported exercise was linked to higher sustained attention but this was not supported by objective MVPA data. Need for increased physical activity and recognition of dips in trait-working memory and trait-sustained attention.